EFFECT OF CHROMIUM PICOLINATE SUPPLEMENTATION IN ARTIFICIAL FEED ON THE GROWTH PERFORMANCE OF HOVEN'S CARP (Leptobarbus hoevenii) FINGERLINGS - Feby Yanti; Adi Susanto; Sumoharjo (Universitas Mataram, 2026)
This study evaluated the effects of dietary chromium picolinate (Cr-Pic) supplementation on the growth performance and feed efficiency of Hoven's carp (Leptobarbus hoevenii) fingerlings, and aimed to determine the optimal dosage. A Completely Randomized Design (CRD) was applied with four treatments and four replications: P0 (0 mg/kg), P1 (1.5 mg/kg), P2 (3.0 mg/kg), and P3 (4.5 mg/kg). The observed parameters included absolute weight gain, total length growth, specific growth rate (SGR), and feed conversion ratio (FCR). The results showed that dietary Cr-Pic supplementation significantly affected (P<0.05) absolute weight gain, total length growth, and FCR, but had no significant effect on SGR. The best performance was observed in treatment P2 (3.0 mg/kg), which produced the highest growth and feed efficiency compared to other treatments. In conclusion, chromium picolinate supplementation at a dose of 3.0 mg/kg feed is recommended to improve growth performance and feed utilization efficiency in Hoven's carp fingerlings.